In 0.49 Ga 0.51 P/GaAs heterojunction bipolar transistors (HBTs) on 200 mm Si substrates : effects of base thickness, base and sub-collector doping concentrations - Wang, Yue (2019)
We report performance of InGaP/GaAs heterojunction bipolar transistors (HBTs) fabricated on epitaxial films directly grown onto 200 mm silicon (Si) substrates using a thin 100% germanium (Ge) buffer layer. Both buffer layer and device layers were grown epitaxially using metalorganic chemical vapor deposition (MOCVD). With the assistance of numerical simulation, we were able to achieve high performance GaAs HBTs with DC current gain of ∼100 through optimizing the base doping concentration (C-doped, ∼ 1.9×1019/cm3), base layer thickness (∼55 nm), and the sub-collector doping concentration (Te-doped, > 5×1018/cm3). The breakdown voltage at base (BVceo) of higher than 9.43 V was realized with variation of < 3% across the 200 mm wafer. These results could enable applications such as power amplifiers for mobile phone handsets and monolithic integration of HBTs with standard Si-CMOS transistors on a common Si platform.